Hubungan Penggunaan Gadget Dengan Pertumbuhan Dan Perkembangan Anak Balita Di Kelurahan Buntu Datu Palopo (Window of Public Health Journal, 2025)
A gadget is a term derived from English, meaning a small electronic device with a specific function. In Indonesian, a gadget is called "acang". Growth is the increase in physical size and structure of part or all of the body so that it can be measured in units of length and weight. Development is the increase in more complex body abilities, such as fine and gross motor skills, speech and language, socialization, and independence. This study aims to determine the relationship between gadget use and the growth and development of toddlers in Buntu Datu Village, Palopo City. The type of research used is an observational analytic with a cross-sectional study approach. The sample was 160 toddlers aged 12-60 months. The instrument used was a pre-screening development questionnaire. The results showed that 100% of toddlers used gadgets. There was a relationship between development (p = 0.037) and growth (p = 0.018) with gadget use in Buntu Datu Village, Palopo City. This study concludes that gadget use is the most influential variable on the growth and development of toddlers in Buntu Datu Village, Palopo City. It is recommended that gadgets be limited so that children's growth and development remain normal.